Polarisasi Moderatisme Islam; Tinjauan Maqashid Syari’ah - A. Halil Thahir (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2018)
For Muslims, the Qur'an and al-Hadith are the main references in Islam. However, in fact Islam appears with various faces. Understanding and expression of Islam becomes diverse, both ideological and political movements. Even not infrequent acts of violence and terrorism in the name of Islam. To bridge very sharp differences, and in order to present a peaceful face of Islam as the message and nature of God (theocentric) and uphold human values (anthropocentric) emerge the spirit of reiterating and making moderate Islam an icon in religion. Islamic moderateism is expected to be a solution to religious extremism which is dangerous for the benefit of the people. Islamic moderateism in the style of maqashid shari'ah reflects moderate Islam which functions revelation, Al-Qur'an and Hadith, reason or reason, as well as proportional social and environmental contexts. Proportionality here still positions revelation as the main source of Islam's existence by being equipped and supported by reason or reason, as well as social and environmental contexts that cannot be ruled out as the source of its teachings. Operationally, the sources of the tersubut teachings can be summarized into: text (al-nash), reality or context (al-waqi'), and subject (al-mukallaf). Nash or text, in the context of moderate Islam - maqasidiy is the source and basis of primary teaching, as a formal object. Whereas al-waqi ', reality or context, is a material-operational object, where the teachings contained in the text and its objectives will be attached to it. While al-mukallaf (subject of teaching) is a person who is intellectually, mentally, and physically ready to accept reality in line with the texts and their maqasid